ANALISIS PENERAPAN AKUNTANSI SEKTOR PUBLIK DALAM PENYAJIAN LAPORAN KEUANGAN MASJID BAITUL AQROM BERDASARKAN ISAK NO. 35 - Indriani, Sarah Aqilah (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2025)
Based on ISAK No. 35, this study investigates the use of public sector accounting in presenting the financial statements of the Baitul Aqram Mosque. Mosques must have a fund management system that can be seen and trusted by them as a non-profit organization responsible for social and religious life. This study applies a descriptive qualitative methodology. Interviews, observations, and documentation of mosque financial statements were used to collect data. One of the topics of analysis is how managers understand ISAK 35, the problems that arise when implementing it, how financial statements must comply with ISAK 35 and how the implementation of these rules impacts the accountability and transparency of financial management. The results of the study indicate that mosque managers still face obstacles in understanding and implementing ISAK 35, but the implementation of this standard contributes positively to improving the quality of financial statements and public trust. This study provides recommendations to improve the implementation of public sector accounting in mosques for more effective and reliable financial management.